Ascitic fluid polymorphic nuclear cell count impacts on outcome of cirrhotic patients with ascites. Issue 5 (1st June 2019) - Simbrunner, Benedikt; Röthenbacher, Annika; Haslacher, Helmuth; Bauer, David; Chromy, David; Bucsics, Theresa; Schwabl, Philipp; Paternostro, Rafael; Scheiner, Bernhard; Trauner, Michael; Mandorfer, Mattias; Schwarzinger, Ilse; et al.
Abstract : Background: Spontaneous bacterial peritonitis (SBP) is defined as an ascitic polymorphonuclear cell count (A‐PMN) > 250 cells/µl. Objective: We aimed to investigate the prognostic value of ascitic fluid cell counts in patients without SBP. Patients and methods: A total of 178 patients were included and stratified by ascitic cell counts at index paracentesis: A‐LEUK‐low (<250/µl), A‐LEUK‐intermediate (250–500/µl) and A‐LEUK‐SBP (>500/µl) for leukocytes; A‐PMN‐low (<125/µl), A‐PMN‐intermediate (125–250/µl) and A‐PMN‐SBP (>250/µl) for PMN cells. Results: One‐year mortality was comparable between group A‐LEUK‐SBP (53.9%) and patients with subclinical cell counts (34.5% for A‐LEUK‐low, 43.5% for A‐LEUK‐intermediate, log‐rank p  = 0.547). However, we observed an increase in one‐year mortality already in group A‐PMN‐intermediate with 75% and A‐PMN‐SBP with 80.9% (vs 40.5% for A‐PMN‐low, log‐rank p  = 0.016). Importantly, increases of A‐PMN cell counts between two paracenteses were associated with increased mortality: per 100 cells/µl increase of absolute A‐PMN cell count: hazard ratio (HR): 1.03 (95% confidence interval (CI): 1.01–1.06), p  = 0.005; per 5% increase of relative PMN cell count: HR: 1.15 (95% CI: 1.06–1.26), p  = 0.001. Conclusion: Patients with PMN cell counts of 125–250/µl are at high risk for mortality, which was very similar to SBP patients with PMN cell counts >250/µl. This highlights the need for preventive strategies. The prognostic value of changes in relative ascitic PMN cell counts should be evaluated in future studies.